QUALITY OF SERVICE AND PRODUCT QUALITY ON CONSUMER SATISFACTION OF TUPPERWARE USERS IN MEDAN - Kalsum, Eka Umi (Accounting and Business Journal, 2022)
This study describes the quality of service and product quality on consumer satisfaction of Tupperware users in Medan. The theory used in this study includes the theory of service quality, product quality, and customer satisfaction. The population in this study is the general public who use Tupperware in Medan as many as 80 people. The data analysis model used is multiple linear regression analysis. The research method uses a descriptive quantitative approach that is supported by a survey, and is explanatory. The results of the study by testing the t-test hypothesis showed that service quality had a positive and significant effect on consumer satisfaction of Tupperware users in Medan. Product quality has a positive and significant effect on consumer satisfaction for Tupperware users in Medan. The results of the F test indicate that service quality and product quality have a positive and significant effect on consumer satisfaction for Tupperware users in Medan. The value of the coefficient of determination (R2 ) of service quality and product quality is able to explain the consumer satisfaction variable of 79.9 % and the remaining 20.1% is influenced by other variables not examined in this study such as price, promotion distribution, and so on.